118k views
5 votes
Simplify 6(x+4)=-2(4x-4)+8x

User Girija
by
5.5k points

1 Answer

7 votes


\huge\mathscr{\colorbox{blue}{\color{yellow}{Answer:}}}


\large{\rightarrow{6\:(x\:+\:4)\:=\:-\:2\:(4x\:-\:4)\:+\:8x}}


\large{\rightarrow{6\:(x\:+\:4)\:=\:-\:2\:(4x\:-\:4)\:+\:8x}}


\large{\rightarrow{6x\:+\:24\:=\:-\:8x\:+\:8\:+\:8x}}


\large{\rightarrow{6x\:+\:24\:=\:{\cancel{-\:8x}}\:+\:8\:+{\cancel{\:8x}}}}


\large{\rightarrow{6x\:+\:24\:=\:8}}


\large{\rightarrow{6x\:=\:8\:-\:24}}


\large{\rightarrow{6x\:=\:16}}


\large{\rightarrow{x\:=\:(-\:16)/(6)}}\\


\large\pink{\boxed{\color{lime}{\rightarrow{x\:=\:(-\:8)/(3)}}}}\\

User A Das
by
5.6k points